2007
DOI: 10.1177/0146167207303951
|View full text |Cite
|
Sign up to set email alerts
|

Without Mercy: The Immediate Impact of Group Size on Lynch Mob Atrocity

Abstract: Two independent research traditions have focused on social contributions to lynching. The sociological power threat hypothesis has argued that lynching atrocity will increase as a function of the relative number of African Americans. The psychological self-attention theory has argued that lynching atrocity will increase as a function of the relative number of mob members. Two series of analyses (one using newspaper reports and the second using photographic records) using different and nonoverlapping samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…Participants also indicated stranger harassment was more likely to occur in group contexts because these behaviors serve a group bonding function. The former finding is consistent with the literature that anonymity (whether it be from the presence of other group members or the absence of individuating information in social interactions) often leads to more extreme and uninhibited behavior (Barak 2005;Coffey and Woolworth 2004;Diener 1979;Diener et al 1976;Kiesler et al 1984;Leader et al 2007;Lee and Leets 2002;Sproull and Kiesler 1986). Our data suggests stranger harassment can be added to this list of behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Participants also indicated stranger harassment was more likely to occur in group contexts because these behaviors serve a group bonding function. The former finding is consistent with the literature that anonymity (whether it be from the presence of other group members or the absence of individuating information in social interactions) often leads to more extreme and uninhibited behavior (Barak 2005;Coffey and Woolworth 2004;Diener 1979;Diener et al 1976;Kiesler et al 1984;Leader et al 2007;Lee and Leets 2002;Sproull and Kiesler 1986). Our data suggests stranger harassment can be added to this list of behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Mullen (1986), for instance, found that interracial violence by Whites against Blacks often occurs within a social context that permits or encourages aggression. His analysis of newspaper reports of Blacks being lynched by White mobs revealed that violence against Blacks was more likely when Whites were part of a larger group and experienced greater anonymity and deindividuation (see also Leader, Mullen, & Abrams, 2007). Thus, factors that normally disinhibit aggressive behavior, such as provocation and anonymity, may be especially potent within intergroup contexts for promoting interracial aggression toward Blacks.…”
Section: From Subtle To Overt Bias: the Inversion Problemmentioning
confidence: 99%
“…Consistent with this notion of anonymity, larger groups have been found to be more violent than smaller groups (McGloin & Piquero, 2009). And, related to group size, Mullen (1986) and Leader et al (2007) examined the atrocity of lynching events through group composition in the form of the Other-Total Ratio, which is calculated as the number of victims in an event divided by the total number of victims and perpetrators at the event. As lynch mobs grew in size, relative to the victims present, mob members committed more atrocious lynchings.…”
Section: Anonymity and Deindividuationmentioning
confidence: 99%
“…The portrayed mob, with blurred faces and bodies melding into a single mass, depicts deindividuation, which is the most common explanation for the atrocity of lynchings (Leader, Mullen, & Abrams, 2007; Mullen, 1986). According to deindividuation, individuals are more likely to break norms and commit atrocious acts when they are anonymous and not self-attentive (Diener, 1980; Festinger, Pepitone, & Newcomb, 1952).…”
mentioning
confidence: 99%